2019
DOI: 10.1021/acsaelm.9b00495
|View full text |Cite
|
Sign up to set email alerts
|

Lateral MoS2Heterostructure for Sensing Small Gas Molecules

Abstract: The potential of a two-dimensional (2D) molybdenum disulfide (MoS2) lateral heterostructure in sensing small gas molecules is being assessed on the basis of quantum mechanical calculations. This heterostructure combines two phases of MoS2, namely, a metallic ribbon embedded within the semiconducting MoS2 phase. In this work the influence on the electronic structure of this 2D material due to the adsorption of gas molecules is investigated. Specifically, the adsorption of NO, NO2, O2, CO, and CO2 on the MoS2 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Zhao et al and Babar et al proposed the structure shown in Figure d in which the NO 2 forms a bridge between Mo sites. Schleicher and Fyta obtained a very similar structure except that the NO 2 appears to be displaced slightly away from the Mo atoms and toward the adjacent S atoms. Finally, Yue et al, Luo et al, Cho et al, and Zhang et al identified the structure in Figure e, with one O atom above a Mo site and the NO 2 projecting into a hollow, which appears to be the lowest in Δ E ads .…”
Section: Resultsmentioning
confidence: 81%
“…Zhao et al and Babar et al proposed the structure shown in Figure d in which the NO 2 forms a bridge between Mo sites. Schleicher and Fyta obtained a very similar structure except that the NO 2 appears to be displaced slightly away from the Mo atoms and toward the adjacent S atoms. Finally, Yue et al, Luo et al, Cho et al, and Zhang et al identified the structure in Figure e, with one O atom above a Mo site and the NO 2 projecting into a hollow, which appears to be the lowest in Δ E ads .…”
Section: Resultsmentioning
confidence: 81%
“…10 The discovery of new 2D materials, such as phosphorene, has shown that these materials may provide much stronger adsorption ability to ambient molecules and gases compared to MoS 2 or InSe. 9,[11][12][13] The promoted activity of phosphorene has been reported for the NO, NO 2 , NH 3 , and CO molecules. 14,15 In addition, the gas sensing ability of phosphorene has been improved by the doping of its surface by NH 3 and NO 2 gas molecules.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it is necessary to further develop gas sensors that can cover SO 2 F 2 and other major SF 6 decomposition gases. With the development of computer science, the DFT method based on quantum mechanics has been widely used in the field of gas sensing [21][22][23][24][25][26][27][28][29][30][31][32]. According to previous research, the material properties calculated by the DFT method have high consistency with the experimental results, which confirms the feasibility of this method in the field of gas sensing.…”
Section: Introductionmentioning
confidence: 68%